Urban Botanical Gardens and the Aesthetics of Ecological Learning: A Theoretical Discussion and Preliminary Insights from Montreal’s Botanical Garden: Part 2: The Human in Nature - Neves, Katja (Anthropologica, 2022)
Although gardens have received relatively little attention from environmental anthropologists, this article suggests that they have great potential as sites for studying the complexity and versatility of human relations with non-humans. By means of a theoretical discussion illustrated through the example of the Botanical Gardens of Montreal (Quebec, Canada), this article scrutinizes the kinds of ecological learning that can occur in urban botanical gardens. It explains how the ephemerality of gardens ultimately leads to the emergence of an ecological aesthetic of attachment, relationship and holism whereby human selves come to conceive of their existence as inextricably linked to non-human selves.